2018
DOI: 10.1039/c8nj02344a
|View full text |Cite
|
Sign up to set email alerts
|

Continuous detection of HCl and NH3 gases with a high-performance fluorescent polymer sensor

Abstract: A novel fluorescent triazine-based covalent organic polymer (COP-1) sensor for HCl and NH3 gases has been designed and synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…20 and 21). The ring protonation of triazine core affecting the red shift have already been reported for some oligomeric/polymeric systems and our observation also complies with it 23,31,33,34 . Further evidence that the site of protonation is indeed the triazine core comes from FT-IR spectroscopy (Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…20 and 21). The ring protonation of triazine core affecting the red shift have already been reported for some oligomeric/polymeric systems and our observation also complies with it 23,31,33,34 . Further evidence that the site of protonation is indeed the triazine core comes from FT-IR spectroscopy (Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…Not only does the emission maximum shift to 660 nm (1.84 eV) upon HCl exposure, but the overall fluorescence is also quenched. Calculations suggest that the triazine ring has a larger hyperpolarisability and more electron withdrawing character than the analogous carbon only benzene core 31 . We therefore conclude that the observed fluorescence quenching of protonated PBHP-TAPT COF is a consequence of electron donation into the protonated triazine ring, an effect that we have previously observed for strong donor-acceptor interactions in triazine-containing, conjugated microporous polymers 31 and for molecular compounds 32 .…”
Section: Resultsmentioning
confidence: 98%
“…Calculations suggest that the triazine ring has a larger hyperpolarisability and more electron withdrawing character than the analogous carbon only benzene core. 31 We therefore conclude that the observed fluorescence quenching of protonated PBHP-TAPT COF is a consequence of electron donation into the protonated triazine ring, an effect that we have previously observed for strong donoracceptor interactions in triazine-containing, conjugated microporous polymers, 31 and for molecular compounds. 32 PBHP-TAPT COF has in principle three potential sites that can act as Lewisbases (Supplementary Figure 15a), so to verify the site at which protonation occurs, we synthesised two model compounds, keto-enamine (KE) and tri-phenyl triazine (TPT) (Supplementary Scheme 2), which mimic the bonding and chemical environments in PBHP-TAPT COF.…”
Section: Resultssupporting
confidence: 62%
“…The ring protonation of triazine core affecting the red shift have already been reported for some oligomeric/polymeric systems and our observation also complies with it. 23,31,33,34 Further evidence that the site of protonation is indeed the triazine core comes from FT-IR spectroscopy (Supplementary Figure 16). None of the signals belonging to the βamino enone bridges or the aromatic backbone of PBHP-TAPT COF see any appreciable changes upon exposure of the material to HCl vapours.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the sensitivity, response time, and reversibility of resonators depend on the chemical structure of the amide group, and they concluded that poly(N,N-dimethylacrylamide) (PDMAA) among the used polymers was the best suited for HCl sensors when considering the relevant data measured using a QCM instrument. Furthermore, they have used various functional polymer-based materials, such as electrodeposited polymer [15], fluorescent polymer [16], poly(N-isopropylacrylamide) (PNIPAM) nanoparticles (NPs) [17][18][19], and PNIPAM brushes [20,21] to detect HCl gas. Despite extensive efforts to develop polymerbased gas sensors, a fabrication process which includes greater simplicity and lower cost should be required to produce efficient gas-sensing platforms.…”
Section: Introductionmentioning
confidence: 99%